Strategies parents use to give children oral medicine: a qualitative study of online discussion forums - Elin Høien Bergene (Scandinavian Journal of Primary Health Care, 2017)
Aim: The aim of this study was to describe strategies parents use to give oral medicine to children. Methods: We conducted an Internet-based qualitative study of posts from online forums where parents discussed how to give children oral medicine. The posts were analyzed using systematic text condensation. The investigators coded and developed groups iteratively, ending up with a consensus on final themes. Results: We included 4581 posts. Parents utilized three main strategies to give oral medicine to children: (1) Open administration give medicine to the child knowingly by changing the palatability, actively involve the child in play or use persuasion; (2) Hidden administration give medicine to the child unknowingly by camouflaging it in food, while sleeping or distracted by another activity; (3) Forced administration force children to take medicine with the use of restraint. Parents expressed three perspectives towards using force: Finding it unproblematic, using force despite not liking it or refusing to use force. No single strategy was described as the obvious first choice, and the strategies were not used in any particular order. Parents who gave up getting their child to ingest the medicine reported to contact the prescriber for a different medication, or stopped the treatment completely. Conclusions: The three strategies are a robust and precise way to categorize techniques used by parents to give children oral medicine. We suggest that health professionals use the strategies to talk to parents and children about administration of oral medicines.